How a slight modification of the bread-making procedure for the evaluation of wheat cultivars affects the most important properties of bread (bread volume and bread crumb) - Živančev Dragan; Jocković Bojan; Mirosavljević Milan; Momčilović Vojislava; Mladenov Novica; Aćin Vladimir; Pribić Milana (Journal on Processing and Energy in Agriculture, 2019)
The aim of the study was to examine how a slight modification of the standard bread-making procedure for the evaluation of wheat cultivars affects bread making properties of different quality samples, without α-amylase activity. For that purpose, two wheat cultivars of different quality (Zvezdana and NS 40S) were examined from four different localities without diastatic activity. Standard physicochemical and rheological parameters for wheat cultivars evaluation were analysed on the eight samples. Also, bread made from flour of these samples was produced according to the standard bread-making procedure for evaluation wheat cultivars and with addition of sugar and malt according to a modified procedure. The results showed that a slight modification of the standard breadmaking procedure can affect the most important properties of bread (bread volume and bread crumb quality). The average values of both parameters were statistically higher. Additionally, statistical analyses showed that bread volume of both cultivars of differing quality was statistically higher, whereas only Zvezdana had statistically higher bread crumb quality.